2005
DOI: 10.1177/0886260505276834
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement in Sexual Coercive Behaviors of Spanish College Men

Abstract: This study aimed to know the prevalence of sexual coercion toward women perpetrated by acquaintance Spanish college men, and some personal factors associated with the involvement in these behaviors to replicate the confluence model. An anonymous questionnaire was completed by 196 university students that included an adaptation of the Sexual Experiences Survey, and other scales to assess different attitudes, motives, and experiences associated with sexual aggression. About 15% of men admitted some involvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 46 publications
6
36
1
1
Order By: Relevance
“…The confluence model has also been replicated and expanded by several independent research teams (Hall, Teten, DeGarmo, Sue, & Stephens, 2005;Knight & Sims-Knight, 2003;Martin, Vergeles, Acevedo, Sanchez, & Visa, 2005;Wheeler et al, 2002). The precise indicators used to assess each of the primary concepts have varied across studies, suggesting that the constructs of impersonal sex and hostile masculinity are robust.…”
Section: Confluence Model Of Sexual Assault Perpetrationmentioning
confidence: 94%
See 1 more Smart Citation
“…The confluence model has also been replicated and expanded by several independent research teams (Hall, Teten, DeGarmo, Sue, & Stephens, 2005;Knight & Sims-Knight, 2003;Martin, Vergeles, Acevedo, Sanchez, & Visa, 2005;Wheeler et al, 2002). The precise indicators used to assess each of the primary concepts have varied across studies, suggesting that the constructs of impersonal sex and hostile masculinity are robust.…”
Section: Confluence Model Of Sexual Assault Perpetrationmentioning
confidence: 94%
“…Although studies with college students are valuable given the high prevalence of sexual assault in that population, more research is needed with community samples. The confluence model was developed with college students (Malamuth et al, 1991(Malamuth et al, , 1995 and most research since then has used college samples (Dean & Malamuth, 1997;Hall, Sue, Narang, & Lilly, 2000;Martin et al, 2005;Wheeler et al, 2002). Only a few researchers have attempted to replicate the confluence model in community samples, and these studies did not include all the relevant variables (Abbey et al, 2006;Knight & SimsKnight, 2003).…”
Section: Limitationsmentioning
confidence: 99%
“…To distinguish between attitudes and motives, and in keeping with Malamuth's strategy, we grouped three attitudes-about-women scales together as conceptual antecedents of hostile masculinity. Numerous researchers have found that perpetrators, in comparison to nonperpetrators, have greater hostility toward women, stronger sexual dominance motives, more traditional attitudes toward gender roles and sexual relationships, and greater acceptance of rape myths (Abbey & McAuslan, 2004;Abbey et al, 2006;Hall et al, 2005;Koss & Dinero, 1988;Malamuth et al, 1991;Malamuth et al, 1995;Martín et al, 2005;Murnen, Wright, & Kaluzny, 2002;Wheeler et al, 2002). Men who are hostile toward women are likely to frequently misperceive women's sexual intentions because they believe that women are disingenuous and play games to get what they want from men.…”
Section: The Confluence Model Of Sexual Assaultmentioning
confidence: 99%
“…Although many researchers have replicated the main effects described by the Confluence model, very few have included a test of the synergy hypothesis. Those researchers who report testing the interaction effect have found that it explains additional variance beyond the main effects of hostile masculinity and impersonal sex (Malamuth et al, 1995;Wheeler et al, 2002;Yost & Zurbriggen, 2006); however, the vast majority of researchers have not evaluated this aspect of the model (Calhoun et al, 1997;Dean & Malamuth, 1997;Hall et al, 2005;Lim & Howard, 1998;Martín et al, 2005;Mosher & Danoff-Burg, 2005;Senn et al, 2000).Malamuth and his colleagues have frequently evaluated the synergy hypothesis through risk analysis (Dean & Malamuth, 1997;Malamuth, 1986;Malamuth et al, 1995;Malamuth et al, 2000). Median or tripartite splits are used to place men in high-or low-risk groups on each variable.…”
mentioning
confidence: 99%
“…A series of studies [19][20][21][22] looks at sexual fantasies, sexual attitudes and other factors in adolescent male sexual offenders, students and nonstudents, which is helpful to understand evolution or maintenance of deviant sexual behaviour. The first study looks at sexual fantasies in male adolescent sexual offenders while they are actually being treated.…”
Section: Characteristics Of Various Types Of Sexual Offenders and Trementioning
confidence: 99%